Pakarangan di Permukiman Desa Singengu Mandailing Julu, Sumatra Utara - Cut Nuraini; Achmad Djunaidi; S Sudaryono; T Yoyok Subroto (Forum Teknik, 2013)
A yard in Singengu Village has a different meaning with a yard in general. Pakarangan or yard in Singengu Village comparises of side area and front area of Bagas (house). It means that the backside area is not a yard. Pakarangan does not has variety vegetation as many house yard, except decorated  plant like flower. The objective of this research is to find out pakarangan concept, factors infuenced its concept and what the meaning of pakarangan phenomenon. This research used phenomenological paradigm with naturalistic approach and inductive-qualitative analysis methode. The result of this research are pakarangan comparises of alaman (space in front of bagas), pamispisan (space beside of bagas) and taruma bagas (space underneath of bagas). The backspace of the house is not part of pakarangan but it is a separate space called parik. The concept of pakarangan is based on Mandailing cosmology's belief about Banua Partoru (bottom word). Parik is cnsidered to Banua Portoru, therefore parik is not a part a pakarangan. The meaning of pakarangan is Singengu village is the whole of  bagas area except parik.Keywords: Pakarangan, Alaman, Bagas, Parik, Banua Partoru